Emerging Approaches for Regulation and Control of CAR T Cells: A Mini Review - Brandt, Lærke J. B.; Barnkob, Mike B.; Michaels, Yale S.; Heiselberg, Julia; Barington, Torben (Frontiers in Immunology, 2020)
Chimeric antigen receptor (CAR) T cells have emerged as a promising treatment for patients with advanced B-cell cancers. However, widespread use and application of the therapy is currently limited by potentially life-threatening toxicities due to a lack of control of the highly potent transfused cells. Researchers have therefore developed several regulatory mechanisms in order to control CAR T cells in vivo. Clinical adoption of these control systems will depend on several factors, including the need for temporal and spatial control, the immunogenicity of the requisite components as well as whether the system allows reversible control or induces permanent elimination. Here we describe currently available and emerging control methods and review their function, advantages and limitations.